2020
DOI: 10.3390/ijms21041220
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in pStat3 Are Involved in Meiotic Spindle Assembly in Mouse Oocytes

Abstract: The signal transducer and activator of transcription 3 (Stat3) is activated upon phosphorylation at Y705 (pStat3) and serves the dual function of signal transduction and transcription activation. Our previous study suggested that pStat3 is functional during oocyte maturation when transcription is silenced. Therefore, we speculated that pStat3 serves other functions. Immunocytochemical analysis revealed that pStat3 emerges at microtubule asters and spindle and is subsequently localized at the spindle poles alon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…The Stat3 -deleted oocytes showed normal maturation, fertilization and preimplantation development [ 65 ]. The current study also showed that the oogenesis was normal when maternal Stat3 was deleted at the primordial follicular stage in Stat3 f / f ( f /−) ; Gdf9 - iCre female mice [ 66 ]. Therefore, STAT3 may be expressed before the primordial follicular stages or have other origins, such as cumulus cells [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The Stat3 -deleted oocytes showed normal maturation, fertilization and preimplantation development [ 65 ]. The current study also showed that the oogenesis was normal when maternal Stat3 was deleted at the primordial follicular stage in Stat3 f / f ( f /−) ; Gdf9 - iCre female mice [ 66 ]. Therefore, STAT3 may be expressed before the primordial follicular stages or have other origins, such as cumulus cells [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, STAT3 inhibitors, Stattic and BP-1-102 were used to analyze the correlation between STAT3 phosphorylation and oocyte maturation. Interestingly, Y705-pSTAT3 plays a novel role of spindle assembly at oocyte maturation [ 66 ]. Those reports indicate that STAT3 plays multiple roles at oogenesis and preimplantation development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were washed and then incubated with Alexa Fluor 488‐anti‐rabbit secondary antibody (1:300, A‐11070, TFS) for OCT4, or Alexa Fluor 488‐anti‐mouse secondary antibody (1:300, A‐11070, TFS) for CD46 at room temperature for 1 h. As a negative control, we reacted the samples with the secondary antibody alone. The samples were transferred onto a glass with SlowFade Diamond Antifade Mountant with DAPI (S36968, TFS) and imaged using a Zeiss LSM780 confocal microscope (Haraguchi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%